2017
DOI: 10.1259/bjr.20160642
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of medical images for radiotherapy applications

Abstract: The high-throughput extraction of quantitative information from medical images, known as radiomics, has grown in interest due to the current necessity to quantitatively characterize tumour heterogeneity. In this context, texture analysis, consisting of a variety of mathematical techniques that can describe the grey-level patterns of an image, plays an important role in assessing the spatial organization of different tissues and organs. For these reasons, the potentiality of texture analysis in the context of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 107 publications
1
108
0
1
Order By: Relevance
“…In our study, eight features were selected for the final model and the minimum training data size was 80. While for the validation sample size, we performed a power calculation to estimate the sample size for our study (26) and found that the minimum sample size is 24. The estimation process can be found in the Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, eight features were selected for the final model and the minimum training data size was 80. While for the validation sample size, we performed a power calculation to estimate the sample size for our study (26) and found that the minimum sample size is 24. The estimation process can be found in the Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, radiomic features that present high classification/prediction power should also present high reliability, since both these properties are necessary to build a reliable radiomic signature. 6,7 In the previous years, several works have dealt with the assessment of radiomic features reliability, both considering the evaluation of repeatability, i.e features that remain the same when calculated multiple times in the same subject with the same conditions, and reproducibility, i.e. features that remain the same when calculated using different acquisition or processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its novel and recent development, there are no standard procedures yet for image processing and features choice and computation. For this reason, the choices made about ROI identification and features calculation have a great impact on the final results . In the present work, particular attention was paid to the image registration and contour propagation processes, in order to correctly and accurately identify the ROIs volumes in which texture analysis was applied, without introducing image interpolation that can alter the gray‐level information.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Mp-MRI could have a compelling role in this context, due to its potentiality to fully characterize the soft tissues from different points of view, such as their anatomical, structural, and functional properties described by the information carried out by different acquisition techniques. Moreover, the combination of mp-MRI and radiomic techniques 15,16 allows the quantification of the tissue's spatial organization by the use of texture analysis. This can improve the knowledge of the muscle response to radiation, by an assessment of the structural changes, which may be dependent on the received dose.…”
Section: Introductionmentioning
confidence: 99%